The Exploratory Factor Analysis of Zadrian-Ifdil Problem Checklist (ZIPC) High-School Version; An Alternative Assessment for Millenials Mental Health Conditions Mapping - Ardi, Zadrian; Ifdil, Ifdil (Universitas Negeri Padang, 2020)
Adolescents face various challenges and changes in order to realize their developmental tasks. The challenges are coupled with the technological disruption that requires adolescents to face new problems that have never existed before as millennials. However, the problems experienced by adolescents are often not expressed because of various obstacles, such as reluctance to tell spontaneously to the adults around them, high social conformity, so it is difficult to find help. For this reason, an alternative assessment is needed, which serves as an effort to map the problems experienced by adolescents and their mental health conditions accurately and actually. This study aims to find the value of the construct validity that forms the ZIPC to be used more widely and measure the actual problem conditions of the assessment subject. Participants involved in this study were 978 high school adolescents from all over Indonesia. The analysis used in finding the construct validity of this instrument is Exploratory Factor Analysis (EFA). The impact of changes and instrument conditions after analysis will be discussed.